Bioinformatics Studies of Flavonoid Derivatives Compound from Saga Rambat Leaves as an Antipyretic Candidate - Ruswanto Ruswanto; Neni Sri Gunarti; Elsa Oktavia Angelica; Himyatul Hidayah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
This research is backed by the frequent use of herbal plants in the community, one of which is the saga (Abrus precatory L.), which is used to reduce body temperature in the Tirtajaya District, Karawang Regency. Saga leaves contain several secondary metabolites with potential antipyretics, one of which is flavonoids. The study aimed to determine the inhibitory activity of flavonoid compounds of saga leaves as inhibitors of COX-2 receptors and IL-1 receptors that reduce fever. The methods used were pharmacokinetic and toxicity studies, molecular docking, and molecular dynamic simulation. The outcomes of molecular docking experiments with seven flavonoid-derived compounds from saga leaves targeting cyclooxygenase-2 (4PH9) receptors revealed that isohemiphloin compounds exhibited the most favorable Gibbs free energy (ΔG) at -7.08 kcal/mol. In the case of interleukin-1 (5R85), cirsimaritin compounds displayed the lowest Gibbs free energy (ΔG) at -7.78 kcal/mol. The analysis of drug screening results indicates that the best compound adheres to four of the five Lipinski rules. Furthermore, the predictions for pharmacokinetics and toxicity are fairly good, as the best compound demonstrates a favorable pharmacokinetic profile and is determined to be non-toxic. These findings collectively suggest that the isohemiphloin compound from saga leaves may be a promising candidate for developing an antipyretic drug, particularly due to its predicted interaction with the cyclooxygenase-2 (4PH9) receptor.